2021
DOI: 10.1039/d1sc01071a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid amplitude-modulation of a diarylethene photoswitch: en route to contrast-enhanced fluorescence imaging

Abstract: A water soluble diarylethene (DAE) derivative that displays exceptionally intense fluorescence from the colorless open form has been synthesized and characterized using UV/vis spectroscopy and fluorescence microscopy. We show that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Numerous photoswitchable fluorescent DAEs have been reported to date, and the main challenge is their extremely low water solubility. Several examples of fluorescent DAEs in living cells and organisms have been reported, [50][51][52][53][54] exploiting strategies to improve solubility such as the introduction of polyethylene glycol chains or charged species. Despite these efforts, only a few of these reports provide characterisation in aqueous conditions, suggesting significant aggregation issues, and the majority function in fluorescence turn-off mode.…”
Section: Intrinsically Fluorescent Photoswitchesmentioning
confidence: 99%
“…Numerous photoswitchable fluorescent DAEs have been reported to date, and the main challenge is their extremely low water solubility. Several examples of fluorescent DAEs in living cells and organisms have been reported, [50][51][52][53][54] exploiting strategies to improve solubility such as the introduction of polyethylene glycol chains or charged species. Despite these efforts, only a few of these reports provide characterisation in aqueous conditions, suggesting significant aggregation issues, and the majority function in fluorescence turn-off mode.…”
Section: Intrinsically Fluorescent Photoswitchesmentioning
confidence: 99%
“…Classical strategies usually require the design of a suitable molecular switch to control the RET process between the switch and various fluorophores (donor-acceptor pairs) according to external stimuli, [4,43b] so that the emission state can be regulated on demand. Andreasson et al [193] reported that the emission of water-soluble DAE derivatives is allowed to be quickly switched using an amplitude-modulated red light with a longer wavelength than that absorbed by the fluorescent species. That example shows great potential for optical lockin detection imaging with high contrast [194] and also provides ideas for overcoming interference from undesired background fluorescence when imaging biological tissues.…”
Section: Bioimagingmentioning
confidence: 99%
“…Andreasson et al. [ 193 ] reported that the emission of water‐soluble DAE derivatives is allowed to be quickly switched using an amplitude‐modulated red light with a longer wavelength than that absorbed by the fluorescent species. That example shows great potential for optical lock‐in detection imaging with high contrast [ 194 ] and also provides ideas for overcoming interference from undesired background fluorescence when imaging biological tissues.…”
Section: Changes In the Physical And Chemical Properties Of Daementioning
confidence: 99%
“…7 Recently, the combination of DTE photoswitching and a fluorescent unit has become a kind of appealing fluorescence switch arising from their thermo-stability, robust fatigue resistance and rapid response. 8–11 A general scheme for designing such switches is a dyad system comprising one fluorophore and DTE unit in the same molecule, facilitating fluorescence quenching through intramolecular energy transfer (ET). 12 As depicted in Scheme 1a, the ring-open state of DTE with high S 1 energy restrains the energy transfer from the excited fluorophore to the open isomer, retaining the fluorescence emission of the fluorophore.…”
Section: Introductionmentioning
confidence: 99%